3D Mass diffusion in ordered nanocomposite systems: Finite element simulation and phenomenological modeling. Issue 1 (21st November 2018) - Zid, Sarra; Zinet, Matthieu; Espuche, Eliane
ABSTRACT: The optimization of polymer barrier properties is currently of crucial importance for a wide range of applications from packaging to building or even energy applications. To meet the requirements of these applications, polymer matrices are often combined with impermeable (nano) fillers. Different nanofiller natures, shapes, and contents have been experimentally used and a large range of barrier materials has been obtained . In the meantime, several numerical approaches have been developed to model gas diffusion properties of nanocomposite materials. However, these approaches often considered bidimensional systems. The aim of this work is to develop 3D Finite Element Model which would be used to predict gas barrier properties of nanocomposites for disk‐shaped nanofillers. The model thus obtained is valid in a wide range of fillers volume fraction values as well as aspect ratios, which makes it possible to go from diluted regimes to semidiluted or even concentrated ones. Furthermore, an analytical equation which describes gas diffusion through nanocomposites films has been built and validated with our finite element modeling model. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2019, 57, 51–61 Abstract : A 3D numerical model using the finite element method is built in order to predict gas barrier properties in nanocomposite systems where fillers, considered as disks, are distributed regularly and uniformly in a unit cell. The specificity of the model is its validity for a wide range of fillers, volume fractions and aspect ratios. A phenomenological analytical model is derived, aiming to predict gas barrier properties of nanocomposites as a function of the parameters describing the fillers, shape and their spatial distribution.